Source and health risks of trace metals in Clarias batrachus and Chrysichthys nigrodigitatus from surface waters in Bayelsa State, Nigeria: a probabilistic model - Izah, Sylvester Chibueze; Richard, Glory; Stanley, Herbert Okechukwu; Sawyer, Wisdom Ebiye; Uwaeme, Onyebuchi Remy; Sylva, Ligeiaziba (Frontiers in Sustainable Food Systems, 2024)
Introduction Human activities have inadvertently led to the release of harmful substances, including trace metals, into aquatic environments, with consequential impacts on aquatic organisms and potential health risks for consumers. This research assessed the presence, origins, and health implications of trace elements within the muscles of Clarias batrachus and Chrysichthys nigrodigitatus from the Bomadi and Gbotebo rivers and their surroundings in Bayelsa State, Nigeria. Methods Thirty samples from each fish species were collected and analyzed to conduct the study. Through the use of an atomic absorption spectrophotometer, the researchers determined the concentrations of trace metals, including iron, copper, zinc, lead, nickel, cadmium, and cobalt, in the fish tissues. Results and discussion The concentrations of the metals within the two fish species varied, with notable differences in zinc and cadmium levels. Utilizing statistical analyses like Pearson correlation, principal component analysis (PCA), and hierarchical cluster analysis (CA), it was established that the trace metals originated from diverse sources. The study then evaluated health risks associated with these trace elements, considering both non-carcinogenic and carcinogenic hazards for different age groups. The results indicated that children’s total target hazard quotient fell below 1 for both fish species, implying a limited tendency toward non-carcinogenic risks through lifelong fish consumption. However, in some adult fish samples, the quotient exceeded 1, indicating a higher potential for non-carcinogenic risks. Regarding carcinogenic hazards, the mean risks were generally lower than the accepted threshold, except for lead in both fish species among adults and children. Stricter values highlighted that only lead concentrations in fish from both categories were deemed acceptable. Consequently, this study highlights the importance of raising awareness among consumers who buy fish from the studied region. Moreover, consistent monitoring of potentially harmful trace elements in water, sediments, and fish is recommended to safeguard consumer health and well-being.